Kontrowersje związane z kryminalizacją przerywania ciąży. Część II - Kania, Agnieszka Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
This article is the second part of a study devoted to the problematic aspects of pregnancy interruption. In the undertaken analysis, some references were made to the draft amendment to the Constitution print 993 of 2007, authors of which insisted on specifying the borderlines of human life’s protection. In the above considerations the attention was paid to the premises, which are necessary to be taken into account in case of potential changing of the abortion law in Poland. Within this scope some references were made especially to: conditions of acknowledgement of the human fetus as an interest protected by penal law, the inter-relations between law and morality, and to the expected profit and loss balance, connected with the increasing criminalization of the pregnancy interruption.
Keywords: pregnancy interruption; abortion; morality; right to protection of life; unborn child; criminalization; protection of life